KONSISTENSI POLITIK LUAR NEGERI MESIR TERHADAP AMERIKA SERIKAT DI ERA MOHAMMAD MURSI - , Hafid Adim Pradana ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The revolution which happening in a country often resulted in a change of the countryâs foreign policy. However, the 2011 Egypt revolution, which followed by the election of Mohammad Mursi from the Muslim Brotherhood as Egypt's first civilian president, it did not change the Egyptian foreign policy, especially towards the United States. This research aims to explain the factors that affect to the consistency of Egyptian foreign policy towards the United States in Mohammad Mursi era. In this research, the author use foreign policy theory which formulated by William D. Coplin and Richard Snyder. This research ultimately found that the consistency of Egyptian foreign policy towards United States in Mohammad Mursi era are affected by several factors including the international context, which can be seen from Egypt 's role as a buffer state of peace in the Middle East which give effect to internal political situation in Egypt, as well as Mursi behavior as policy makers which caused by his perception of a look at the internal setting such as internal political situation in Egypt, and the external settings such as Egypt and U.S. relations in the economic field. The Mursi perception can not be separated from his background as moderate cadre of the Muslim Brotherhood.